THE DIFFERENCE PROBLEM SOLVING SKILLS OF PHYSICS WHO ARE TAUGHT USING THE PROJECT BASED LEARNING MODEL WITH PROBLEM BASED LEARNING - Masringgit Marwiyah Nst; Motlan Motlan; Alkhafi Maas Siregar (Jurnal Pendidikan Fisika, 2020)
This study aims to determine the students' physics problem solving skills taught by the Project Based Learning and Problem Based Learning models in the material of optical instruments in class XI Semester II MAN 1 Medan T.P 2018/2019. This type of research is quasi-experimental. The population in the study were all students of class XI Semester II MAN 1 Medan consisting of 7 MIA classes totaling 329 students. Sampling was done by random sampling by taking 2 classes from 7 classes randomly, namely class XI MIA-5 as an experimental class with PBL model totaling 40 people and class MIA-1 as an experimental class with a PjBL model of 40 people. The instrument used to find out problem solving skills is a test of learning outcomes in the form of essays with a number of 7 questions and in this study assisted by three observers to assist researchers in carrying out their research. From the results of posttest data processing, it was found that the significance value was smaller than 0.05, H_0 was rejected and accepted H_a or There were differences in students' physics problem solving skills taught with the PJBL model and PBL models